Impact of low bone mass and antiresorptive therapy on antibiotic efficacy in a rat model of orthopedic device‐related infection. Issue 2 (23rd December 2020) - Thompson, Keith; Freitag, Linda; Styger, Ursula; Camenisch, Karin; Zeiter, Stephan; Arens, Daniel; Richards, R. Geoff; Moriarty, Thomas F.; Stadelmann, Vincent A.
Abstract: A significant proportion of orthopedic devices are implanted in osteoporotic patients, but it is currently unclear how estrogen deficiency and/or exposure to antiresorptive bisphosphonates (BPs) influence orthopedic device‐related infection (ODRI), or response to therapy. The aim of this study is to characterize the bone changes resulting from Staphylococcus epidermidis infection in a rodent ODRI model and to determine if ovariectomy (OVX) or BP treatment influences the infection or the success of antibiotic therapy. A sterile or S. epidermidis ‐contaminated screw was implanted into the proximal tibia of skeletally mature female Wistar rats ( n  = 6–9 per group). Bone changes were monitored over 28 days using in vivo micro‐computed tomography scanning. OVX was performed 12 weeks before screw implantation. The BP zoledronic acid (ZOL) was administered 4 days before screw insertion. A combination antibiotic regimen (rifampin plus cefazolin) was administered from Days 7–21. In skeletally healthy animals, S. epidermidis induced marked changes in bone, with peak osteolysis occurring at Day 9 and woven bone deposition and periosteal mineralization from Day 14 onwards. Antibiotic therapy cleared the infection in the majority of animals (2/9 infected) but did not affect bone responses. OVX did not affect the pattern of infection‐induced changes in bone, nor bacterial load, but reduced antibiotic efficacy (5/9 infected). ZOL treatment did not protect from osteolysis in OVX animals, or further affect antibiotic efficacy (5/9 infected) but did significantly increase the bacterial load. This study suggests that both BPs and OVX can influence host responses to bone infections involving S. epidermidis .